Results of endoscopic transcanal tympanoplasty performed by a young surgeon in a secondary hospital - Gokgoz,Mert Cemal (2020)
Abstract Introduction: Tympanoplasty is performed to close the tympanic membrane perforation and recover the hearing level of patients with non-suppurative chronic otitis media. Endoscopic tympanoplasty has recently been increasingly preferred by ear nose and throat surgeons to treat tympanic membrane perforations. Objective: The aim of this study is to discuss the outcomes of patients undergoing endoscopic tympanoplasty performed by a young surgeon in a secondary hospital in the context of the literature. Methods: Fifty patients undergoing endoscopic Type 1 tympanoplasty between February 1, 2017 and February 1, 2018, were included. The patients' age, gender, perforation side and size, preoperative and postoperative pure tone audiometry, graft failure, postoperative pain and complication status were evaluated. Results: The graft success rate was 94% at 6 months postoperatively. Audiometry thresholds were obtained at frequencies of 0.5, 1, 2 and 4 kHz. Preoperative pure tone audiometric thresholds were 41.6, 36.3, 34.1, and 39.1 dB, and postoperative, 6 months after surgery, 19.5, 17.8, 17.5, and 20.8 dB. Pure tone audiometry air-bone gaps at the same frequencies changed from 30.5, 24.6, 22.2, and 28.6 dB preoperatively, to 11.0, 9.3, 8.6, and 13.9 dB 6 month after the surgery. There was a statistically significant improvement between the preoperative and postoperative pure tone audiometry, and air bone gaps at all measured frequencies (p < 0.05). Conclusion: Endoscopic transcanal cartilage tympanoplasty has become more commonly performed by otolaryngologists due to the shortening of operation and hospitalization times as well as similar audiological results to those obtained with microscopic tympanoplasty. The surgical and audiological results of a young ear nose throat specialist can reach a similar level of success to those of experienced surgeons, due to a fast learning curve.